Double-Blind Placebo-Controlled Pilot Investigation of the Safety of a Single Dose of Rapid-Acting Intranasal Insulin in Down Syndrome - Michael Rosenbloom; Terry Barclay; Justin Johnsen; Lauren Erickson; Aleta Svitak; Maria Pyle; William Frey; Leah R. Hanson (Adis, Springer Healthcare, 2020)
Abstract Background Individuals with Down syndrome are likely to develop clinical and neuropathological brain changes resembling Alzheimer's disease dementia by the ages of 35-40 years. Intranasal insulin is a potential treatment for neurodegenerative disease that has been shown to reduce amyloid plaque burden and improve verbal memory performance in normal as well as memory-impaired adults. Investigations have shown that rapid-acting insulins may result in superior cognitive benefits compared with regular insulin. Objectives The primary objective of this study was to measure the safety and feasibility of intranasal rapid-acting glulisine in subjects with Down syndrome. Secondarily, we estimated the effects of intranasal glulisine on cognition and memory in Down syndrome. Methods A single-center, single-dose, randomized, double-blind, placebo-controlled, cross-over pilot study was performed to test the safety of intranasal glulisine vs placebo in 12 subjects with Down syndrome aged ≥ 35 years. Intranasal administration utilized the Impel NeuroPharma I109 Precision Olfactory Delivery (POD®) device. The primary outcomes were the occurrence of any or related adverse and serious adverse events. Secondary post-treatment cognitive outcome measures included performance on the Fuld Object-Memory Evaluation and Rivermead Behavioral Memory Test. Results Intranasal glulisine was safe and well tolerated in the Down syndrome population. No adverse or serious adverse events were observed. Conclusions Further investigations are necessary to better evaluate the potential cognitive-enhancing role of intranasal insulin in the Down syndrome population. ClinicalTrials.gov ID NCT02432716.